Investigation of fracture prevalence of instruments used in root canal treatments at a faculty of dentistry: a prospective study - Eskibaglar, Mehmet; Ozata, Merve Yeniceri; Ocak, Mevlut Sinan; Oztekin, Faruk (Korean Acad Conservative Dentistry, 2023)
Objectives: The aim of this study was to examine the use of hand or rotary files by pre-graduation (fourth- and fifth-year) and postgraduate students in endodontic treatments and to determine the incidence of file fracture and the management of cases with broken instruments. Materials and Methods: A total of 2,168 teeth undergoing primary endodontic treatment were included in this study. It was determined that 79 of these teeth resulted in broken tools. In the case of broken tools, the education level of the treating clinician, the tooth that was being treated, the canal and fracture level, the curvature of the tooth and the management of the broken instrument were recorded. Periapical radiographs of the patients were used to calculate curvature following the Schneider method. Results: There was no significant difference in the incidence of broken tools according to education level (p > 0.05). The incidence of file fracture in molar teeth (73.4%) was higher than in other teeth (p < 0.05). More files were broken in the mandibular molar MB canal (20.25%) and in the apical third of the canals (72.1%). The risk of instrument fracture was high in teeth with moderate (44.3%) and severe (38%) curvature canals. The management of apically broken (80%) files mostly involved lefting (p < 0.05). Conclusions: There was no statistically significant difference between fourth-year students, fifth-year students and postgraduate students in terms of instrument fracture.
Keywords: Endodontic file; File fracture; File fracture management; Separate file